The effect of e-service quality on customer trust in McD Serang - Arisa, Ilham; Siregar, Santa Dameria; Aisah, Siti; Wahyudi, Wahyudi (Institute of Computer Science (IOCS), 2024)
Electronic services combine two trends: the shift of the conventional economy due to the expansion of the information economy and the digital network system, which includes e-services. As a large fast-food business in the world, McD has innovated by presenting electronic services, where services can be provided using a large screen and ordering is done independently by customers. This supports this research to determine how much influence the e-service quality provided by McD has on customer trust. This research was conducted using descriptive quantitative methods with data analysis tests in the form of a validity test, reliability test, classical assumption test (including normality test and linearity test), simple linear regression test, and correlation test. The target in this research is McD Serang City customers with a population of 730,530 people in Serang City, and a sample was taken using the Slovin formula with an error rate of 10%, resulting in 99.98 rounded up to 100 respondents. Based on the results of the data analysis test carried out, it is known that based on the simple linear regression test that the t value is 10,290> t table 6,660 with a significance level of 0.000 <0.05, it states that e-service quality (x) on customer trust (y) has a significant influence. As for the amount of influence, it can refer to the coefficient of determination test results, which has the amount of influence of variable x on variable y, namely 0.519 (51.9%).